2013
DOI: 10.1007/s10897-013-9630-2
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Burden of Sickle Cell Disease on Parents with an Affected Child in Cameroon

Abstract: The chronicity of Sickle Cell Disease (SCD) could impair the quality of life of caregivers. We performed a quantitative study to assess various indices of psychosocial burden on Cameroonian parents (N = 130) with at least one living SCD-affected child. Demographic and medical information were obtained from the participants and the review of the patients' medical records. The survey instrument included a 38-item stress factors scale using Likert-type statements, evaluating general perceptions of stress and five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 23 publications
4
41
0
Order By: Relevance
“…The proportion of doctors who accepted TAP for SCD (40.9%) could be still considered high as well. But a more interesting thing is that the proportion is similar to support for voluntary abortion that we reported earlier (Wonkam and Hurst, 2007), and much lower than the support doctors gave to medical abortion in principle (90.1%; Fig. 2A).…”
Section: Wonkam and Hurst Discussionsupporting
confidence: 61%
“…The proportion of doctors who accepted TAP for SCD (40.9%) could be still considered high as well. But a more interesting thing is that the proportion is similar to support for voluntary abortion that we reported earlier (Wonkam and Hurst, 2007), and much lower than the support doctors gave to medical abortion in principle (90.1%; Fig. 2A).…”
Section: Wonkam and Hurst Discussionsupporting
confidence: 61%
“…Pain crisis was the event that most contributed to a greater burden of disease on Cameroonian parents. 26 In respect to this severe clin ical profile, GuimarĂŁes and collaborators, 14 in their study on the daily lives of families of children and adolescents with sickle cell disease, reported that mothers tend to be overprotective and burdened when they need to spend time caring for their children and have to give up social functions. An impact on the family environment was also reported in this study, namely the inability to accept the disease and the fear of death, to the extent that the family experienced periods of greater or lesser control of the disease and could not handle the situation, feeling lost and hopeless.…”
Section: Discussionmentioning
confidence: 99%
“…Complications such as hospitalisation associated with pain crises may impair the academic achievement of carers which then exacerbates the financial burden of SCD (Wonkam et al, 2014). Thomas et al (1992) also argued that support and family functioning lead to better adjustment and reduced psychological complications of SCD for adults.…”
Section: The Management Of Scdmentioning
confidence: 99%
“…Consideration of the interrelationship of all factors is thus integral to the management of this disorder. Parents of children affected with SCD confront psychosocial burdens that negatively influence the quality of life of the whole family, and thus pose difficulties in coping with the disease (Wonkam et al, 2014). The family provides additional attention and continuous monitoring when caring for children with SCD which, in turn, may influence the care provided to siblings (Graff et al, 2012).…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation